The Power of Tax Knowledge: Key Factors to Boost Tax Compliance - Santosa, Agus; Rahman, Abdul; Fadillah, Syarif; Fadilla, Sarah (Jurnal Borneo Administrator, 2025)
Taxes are the primary source of state revenue in Indonesia today. The government has made various efforts to increase tax revenues. Unfortunately, Indonesia's tax compliance remains low, as evidenced by its relatively low tax ratio compared to other Asian countries. One intrinsic factor influencing tax compliance is tax morale, which is shaped by an individual's understanding of taxation and their perception of the tax system. This study examines whether a person's tax understanding affects their compliance. Using a quantitative approach and focusing on MSME actors in Cianjur Regency, the research reveals a positive and significant relationship between tax understanding and tax compliance. Notably, the study identifies three main factors that influence a person's understanding of taxes: knowledge of the importance of having role models in tax administration, awareness of the significance of transparency in tax management, and understanding of tax systems that are free from corruption. These findings are novel because they highlight the critical role ofcomprehensive tax education in fostering higher tax morale and compliance levels among MSMEs. This study contributes to the literature by offering insights into how improved understanding of taxation, supported by ethical and transparent practices, can lead to better tax compliance, particularly in the digital era.